2016
DOI: 10.1016/j.kjms.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tadalafil and pentoxifylline on apoptosis and nitric oxide synthase in liver ischemia/reperfusion injury

Abstract: The aim of this study was to investigate the effects of tadalafil (TDF) and pentoxifylline (PTX) on hepatic apoptosis and the expressions of endothelial and inducible nitric oxide synthases (eNOS and iNOS) after liver ischemia/reperfusion (IR). Forty Wistar albino rats were randomly divided into five groups (n=8) as follows: sham group; IR group with ischemia/reperfusion alone; low-dose and high-dose TDF groups received 2.5 mg/kg and 10 mg/kg TDF, respectively; and PTX group received 40 mg/kg PTX. Blood was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…PDE5i have also shown to ameliorate ischemic damage in animal models of myocardial infarction (Koka et al, 2013, renal ischemia (Kucuk et al, 2012, Medeiros et al, 2010, Zahran et al, 2015, liver ischemia (Bektas et al, 2016), testicular torsion (Zavras et al, 2014, Yildiz et al, 2012, Erol et al, 2009, and ovarian ischemia (Arikan et al, 2010) through antiapoptotic and anti-oxidative stress mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…PDE5i have also shown to ameliorate ischemic damage in animal models of myocardial infarction (Koka et al, 2013, renal ischemia (Kucuk et al, 2012, Medeiros et al, 2010, Zahran et al, 2015, liver ischemia (Bektas et al, 2016), testicular torsion (Zavras et al, 2014, Yildiz et al, 2012, Erol et al, 2009, and ovarian ischemia (Arikan et al, 2010) through antiapoptotic and anti-oxidative stress mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Tadalafil has a longer half-life, and greater selectivity for PDE5 than sildenafil (18). In a recent study by Bektas et al (18), tadalafil (10 mg/kg) prevented ROS damage, lipid peroxidation, hepatocyte necrosis, and apoptosis in rat liver ischemia/reperfusion injury and minimized liver damage. In a zymosan-induced rat model of arthritis, tadalafil (0.02-0.5 mg/kg, per oral) dose-dependently decreased neutrophil influx and tumor necrosis-alpha release into the synovial cavity (46).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, sildenafil citrate (5 mg/kg per day) for 3 days showed significant protection in a rat acetic acid-induced colitis model via its actions on oxidant/ antioxidant status (45). Tadalafil has a longer half-life, and greater selectivity for PDE5 than sildenafil (18). In a recent study by Bektas et al (18), tadalafil (10 mg/kg) prevented ROS damage, lipid peroxidation, hepatocyte necrosis, and apoptosis in rat liver ischemia/reperfusion injury and minimized liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted to show the eNOS activity following liver and kidney damage, because its decrease and imbalance with endothelin synthesis increase vascular resistance. Using tadalafil and pentoxifylline against liver I/R damage, Bektas et al [48] observed the prevention of oxidative stress, lipid peroxidation, and hepatocyte damage and thus reported a minimisation of endothelial damage. Potent eNOS activity was observed in the I/R group.…”
Section: Discussionmentioning
confidence: 99%